The 33 Strategies of War - Greene, Robert (New Delhi Viva Books Private Limited, 2006)
Draws on some of history's most effective military tactics and the examples of such figures as Napoleon, Margaret Thatcher, and Ulysses S. Grant to outline psychological strategies for effective negotiating, responding to dangerous situations, and managing life milestones.
Include Bibliography
Keywords: Conduct of Life -- Strategy -- Military Art and Science